Dates on Literary Ostraca: A Case Study - Jurjens, Judith (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
This paper presents an analysis of the dates found on ostraca containing the literary composition The Teaching of Khety , also known as The Satire of the Trades . Various aspects of these dates are discussed, for example the palaeography and the placement of the dates on the ostracon, for the purpose of outlining some scribal practices in ancient Egypt. From the dates themselves can be deduced that scribes conducted their literary activities all year round, both during the working week and at the weekend. Finally, the presumed educational context of the ostraca is discussed. The high percentage of dates on ostraca with Khety , in comparison to other literary compositions, suggests Khety was the most popular text used in the training of scribes.